Targeting of human and mouse T-lymphocytes by monoclonal antibody-HPMA copolymer-doxorubicin conjugates directed against different T-cell surface antigens - Jelínková, M; Strohalm, J; Plocová, D; Subr, V; St'astný, M; Ulbrich, K; Ríhová, B (Journal of controlled release, 1998)
Binding of HPMA copolymer-conjugated doxorubicin targeted with monoclonal antibodies directed against various T-cell surface receptors, i.e. Thy1.2 (CDw90), I-A (MHC class II. glycoprotein), L3T4 (CD4), IL-2R (CD25) and CD3, is considerably increased in Con A stimulated T-lymphocytes. FACS analysis showed that the binding is most intensive with anti-Thy1.2 and anti-L3T4 targeted derivatives and it is proportional to the antiproliferative effect of the antibody-targeted drug. No binding and no antiproliferative capacity was observed after in vitro incubation of mouse T-cells with a nonspecific mouse IgG-HPMA-DOX conjugate. [3H]-TdR incorporation was inhibited considerably more in Con A stimulated T-cell culture and in EL4 mouse T-cell lymphoma as compared with the culture of nonactivated T-lymphocytes. This proves that intensively proliferating cells are more susceptible to the inhibitory action of an antibody-targeted drug. The cytotoxic efficacy of HPMA copolymer with GlyPheLeuGly or GlyLeuPheGly side-chains to which the drug is conjugated was superior to HPMA copolymer with GlyPheGly or GlyLeuGly side-chains. However, there is no direct correlation between the rate of in vitro drug release and the in vitro cytotoxicity of the respective conjugates. This suggests that the rate of drug release from the conjugate is only one factor responsible for the pharmacological efficacy of the preparation. Furthermore, we detected substantial and prolonged inhibition of proliferation of Con A activated T-cells only if doxorubicin was injected in vivo in the form of an anti-Thy1.2-targeted conjugate.
Keywords: T-Lymphocytes; Concanavalin A; Polymethacrylic Acids; Amino Acid Sequence; Doxorubicin; Animals; Lymphocyte Activation; kyseliny polymethakrylové; Humans; Mice; Mice, Inbred BALB C; sekvence aminokyselin; Antigens, Surface; doxorubicin; radioizotopy jodu; krysa rodu Rattus; monoklonální protilátky; konkanavalin A; Rats; aktivace lymfocytů; Antibodies, Monoclonal; nosiče léků; myši inbrední BALB C; zvířata; Drug Carriers; lidé; antigeny povrchové; T-lymfocyty; Iodine Radioisotopes; myši